Analisis Determinan Paktik Manajemen Laba Pada Bank Umum Syariah di Indonesia - Fitriani Saragih; Rahmat Daim Harahap; Saparuddin Siregar (Jurnal Riset AKuntansi dan Bisnis, 2023)
This study aims to examine the determinants of factors influencing the management of earnings management practices in Islamic banks in Indonesia. The factors affecting earnings management are reflected in the Camel Ratio in the form of capital adequacy, return on assets, return on equity and financing to deposit ratio. The population in this study are all Islamic commercial banks in Indonesia, with a sample of 60 companies. The data analysis technique used in this research is multiple linear regression. The results of this study indicate that CAR, RORA, ROE have no significant effect on earnings management, then the FDR variable has a significant effect on earnings management and furthermore, together the variables CAR, RORA, ROE and FDR have an influence on earnings management at banks. general sharia in Indonesia.